Microbiome dysbiosis and alcoholic liver disease(☆) - Li, Fengyuan (Liver Res, 2019)
Microbiome dysbiosis is strongly associated with alcoholic liver disease (ALD). Recent studies on comprehensive analyses of microbiome compositional and functional changes have begun to uncover the mechanistic relation between microbiome and the pathogenesis of ALD. Importantly, targeting the microbiome has become a potential strategy for the prevention and treatment of ALD. In this review, we summarize the clinical evidence of microbiome dysbiosis in ALD patients, and experimental advances in microbiome and metabolomic functional changes in animals with different species and genetic backgrounds in ALD. We also summarize the studies in humanized intestinal microbiome and fecal microbiota transplantation in mice. We introduce new developments in the studies on the role of the circulating bacterial microbiome, oral bacterial microbiome and fungal microbiome in the development of ALD. We highlight the potential mechanisms by which microbiome dysbiosis contributes to ALD, including short chain fatty acid changes, bile acid metabolism, intestinal barrier function, release of bacterial and fungal products, and inflammation. In addition, we summarize the recent developments targeting the microbiome in prevention and treatment of ALD, including dietary nutrient interference, herbal medicine, antibiotics, anti-fungal agents, probiotics, engineered bacterial therapy, fecal transplantation and oral hygiene. Although recent preclinical studies have advanced our understanding of the microbiome and ALD, clinical studies, especially prospective studies with large samples, are needed to better understand the cause-effect of microbiome dysbiosis in ALD. Identifying new precision-based strategies targeting the microbiome are expected to be developed as more effective therapies in ALD.